2016
DOI: 10.1111/jopr.12477
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fracture Resistance and Stiffness of Heat‐Polymerized High Impact Acrylic Resin with Localized E‐Glass FiBER FORCE® Reinforcement at Different Stress Points

Abstract: Placement of the GFF close to the tensile stress side surface of the bar increased the resistance to elastic deformation (i.e., higher MOE or stiffness) and the stress level needed for flexural fracture (i.e., higher FS). In addition, more energy was absorbed by reinforced specimens before fracture occurred (i.e., higher toughness). Localized reinforcement targeting tensile stress centers is thus a practical way to improve clinical durability of dentures against intra- and extraoral fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 35 publications
(54 reference statements)
3
29
0
Order By: Relevance
“…Therefore, the higher the number of fiber layers added in the tensile stress zone, the more the fracture strength of the IOD. This is in line with the findings by Dyer et al (37) and Agha et al (38) regarding the quantity of fibers added to the tensile stress zone of prostheses. However, it disagrees with the finding by Kanie et al (23), who found that the increase in the number of fiber layers does not increase the fracture strength.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, the higher the number of fiber layers added in the tensile stress zone, the more the fracture strength of the IOD. This is in line with the findings by Dyer et al (37) and Agha et al (38) regarding the quantity of fibers added to the tensile stress zone of prostheses. However, it disagrees with the finding by Kanie et al (23), who found that the increase in the number of fiber layers does not increase the fracture strength.…”
Section: Discussionsupporting
confidence: 82%
“…To evaluate these treatments, a three-point bending test was performed. This test is the most used to evaluate acrylic resin resistance [1][2][3]7,[10][11][12]14,21,22] failure caused by deformation of the base of the complete prosthesis [3,12,14], being preferable to torsion, compression or shear tests [7]. Trying to simulate the conditions of a complete prosthesis, the thickness of the experimental bars was 2.5 mm, which is the dimension also used in others researches [7,[11][12] and it is close to the one clinically used in a prosthesis base.…”
Section: Discussionmentioning
confidence: 99%
“…Its use is justified not only for the simplicity of the technique, but also good resistance, durability, biocompatibility, cost-benefit ratio, dimensional and chemical stability. However, it still does not fulfill all the necessary requirements of a rehabilitation material [1][2][3][4][5]. Complete dentures execution with TAAR are done at the cost of clinical and laboratory procedures [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations